Distribution of Bacterial Strains and their Antibiotic Sensityvity Profile in an Urban Referral Hospital - Hasan, M Bulbul; Nahar, S Gul; Ali, M Nawshad; Khatun, Mst Rokeya; Das, Chinmoy Kanti (TAJ: Journal of Teachers Association, 2018)
Then Present study was done to assess the distribution of bacterial pathogens with their pattern of antibiotic susceptibility in an urban referral hospital in RMCH. A total of 393 bacteria strains were isolated from various specimens over a 10-months period. The majority of the organisms were Escherichia coli (33.33%) followed by Klebsiella species (27.48%), staphylococcus aureus (17.05%), Acinetobcter species (8.14%), Pseudomonas species (7.12%), and others. The third-generation Cephalosporins like Ceftriaxone, Ceftazidime and Cefotaxime were sensitive to Ciprofloxacin of various Enterobacteriaceae was only between 33-40% compared to 52.8-37.9% against Gentamicin. Majority of the Enterobacteriaceae were resistant to Ampicillin, whereas almost all of the Enterobacteriaceae (94-100%) were sensitive to Imipenem. About 97.0% Acinetobacter species were susceptible to Imipenem. Sensitivity of the organism (Acinetobacter) to third-generation Cephalosporins ranged between 50-56%, whereas 40.6% were found sensitive to Ciprofloxacin. The sensitivity to Chloramphenicol, Co-trimixazole, Cephalexin and Ampicillin ranged between 9.3% to 34.3%. About 93.0% of Pseudomonas species were sensitive to Imipenem. The rate of susceptibility to Gentamicin and Netilmicin was higher than those of the Ciprofloxacin and Ceftriaxone (37.8% and 53.5% vc. 39.2%). About 70% of isolated S. aureus were resistane of Oxacillin but all were sensitive to Vancomycin. The result of this study would help the physicians to make a judicious choice of antibiotics for therapeutic purposes. TAJ 2012; 25: 72-76